Rethinking of international exchange and intercultural learning into Indonesian pre‐service teachers in the pandemic recovery: A narrative inquiry (Universitas Negeri Semarang, 2022)
One of teacher education goals is to produce interculturally competent educators; teach students in multicultural classrooms and prepare them in an increasingly globalized world. In response to this critical need in teacher preparation, international exchange attempts at developing those competencies. It is in accordance with Walters and Walters' (2009) principle,